Novel photochemical reactions of carbocyclic diazodiketones without elimination of nitrogen – a suitable way to N-hydrazonation of C–H-bonds - Rodina, Liudmila L.; Azarova, Xenia V.; Medvedev, Jury J.; Semenok, Dmitrij V.; Nikolaev, Valerij A. (Beilstein Journal of Organic Chemistry, 2018)
The sensitized photoexcitation of 2-diazocyclopentane-1,3-diones in the presence of THF leads to the insertion of the terminal N-atom of the diazo group into the α-С–Н bond of THF, producing the associated N-alkylhydrazones in yields of up to 63–71%. Further irradiation of hydrazones derived from furan-fused tricyclic diazocyclopentanediones culminates in the cycloelimination of furans to yield 2-N-(alkyl)hydrazone of cyclopentene-1,2,3-trione. By contrast, the direct photolysis of carbocyclic diazodiketones gives only Wolff rearrangement products with up to 90–97% yield.
Keywords: C–H insertion; diazo compounds; excited state; photochemistry; Wolff rearrangement

(untitled) - Ford, A.; Miel, H.; Ring, A.; Slattery, C. N.; Maguire, A. R.; McKervey, M. A. (Chem. Rev., 2015)

(untitled) - Galkina, O. S.; Rodina, L. L. (Russ. Chem. Rev., 2016)

(untitled) - Candeias, N. R.; Afonso, C. A. M. (Curr. Org. Chem., 2009)

(untitled) - Zhang, Z.; Wang, J. (Tetrahedron, 2008)

(untitled) - Kirmse, W. (Eur. J. Org. Chem., 2002)

Carbene Chemistry - Bertrand, G. (Marcel Dekker, 2002)

Kinetics and Spectroscopy of Carbenes and Biradicals - Platz, M. S. (Plenum Press, 1990)

Carbene Chemistry - Ross, M. J.; Moss, R. A. (John Wiley & Sons Inc., 1975)

Carbenes - Moss, R. A.; Jones, M., Jr (John Wiley & Sons, 1973)

Carbenes - Kirmse, W. (Academic Press, 1971)

(untitled) - Tidwell, T. T. (Angew. Chem., Int. Ed., 2005)

(untitled) - Garbarino, S.; Banfi, L.; Riva, R.; Basso, A. (J. Org. Chem., 2014)

(untitled) - Burdzinski, G.; Kubicki, J.; Sliwa, M.; Réhault, J.; Zhang, Y.; Vyas, S.; Luk, H. L.; Hadad, C. M.; Platz, M. S. (J. Org. Chem., 2013)

(untitled) - Willumstad, T. P.; Haze, O.; Mak, X. Y.; Lam, T. Y.; Wang, Y.-P.; Danheiser, R. L. (J. Org. Chem., 2013)

(untitled) - Burdzinski, G.; Zhang, Y.; Wang, J.; Platz, M. S. (J. Phys. Chem. A, 2010)

(untitled) - Wolpert, D.; Schade, M.; Brixner, T. (J. Chem. Phys., 2008)

(untitled) - Nikolaev, V. A.; Shevchenko, V. V.; Platz, M. S.; Khimich, N. N. (Russ. J. Org. Chem., 2006)

(untitled) - Popik, V. V. (Can. J. Chem., 2005)

(untitled) - Korneev, S. M. (Eur. J. Org. Chem., 2011)

(untitled) - Shevchenko, V. V.; Khimich, N. N.; Platz, M. S.; Nikolaev, V. A. (Tetrahedron Lett., 2005)

(untitled) - Bogdanova, A.; Popik, V. V. (J. Am. Chem. Soc., 2004)

Chemistry of diazirines - Meier, H. (Diazirine-Diazoalkane Interconversions, 1987)

(untitled) - Nikolaev, V. A.; Khimich, N. N.; Korobitsyna, I. K. (Chem. Heterocycl. Compd., 1985)
Khim. Geterotsikl. Soedin. 1985, 321–325.

(untitled) - Livinghouse, T.; Stevens, R. V. (J. Am. Chem. Soc., 1978)

(untitled) - Voigt, E.; Meier, H. (Chem. Ber., 1975)

(untitled) - Lowe, G.; Parker, J. (J. Chem. Soc. D, 1971)

(untitled) - Rodina, L. L.; Baranovskii, V. I.; Galkina, O. S.; Nikolaev, V. A.; Tonogina, N. L.; Povolotskiy, A. V. (J. Org. Chem., 2017)

(untitled) - Rodina, L. L.; Galkina, O. S.; Maas, G.; Platz, M. S.; Nikolaev, V. A. (Asian J. Org. Chem., 2016)

(untitled) - Nikolaev, V. A.; Galkina, O. S.; Sieler, J.; Rodina, L. L. (Tetrahedron Lett., 2010)

(untitled) - Galkina, O. S. (Saint-Petersburg State University, 2015)

(untitled) - Presset, M.; Mailhol, D.; Coquerel, Y.; Rodriguez, J. (Synthesis, 2011)

Eur. Pat. Appl. - Wu, C.; Mooring, A. M.; Yardley, J. T. (UV photoresist containing polycyclic cyclopentanediazodione derivative, 1991)

Patent of the USSR - Korobitsyna, I. K.; Rodina, L. L.; Nikolaev, V. A. (The method of producing bicyclic diazocyclopentanediones, 1983)

Diazo Compounds. Properties and Synthesis - Regitz, M.; Maas, G. (Academic Press, 1986)

Modern Catalytic Methods for Organic Synthesis with Diazo Compounds - Doyle, M. P.; McKervey, M. A.; Ye, T. (John Wiley & Sons Inc., 1998)

(untitled) - Baum, J. S.; Shook, D. A.; Davies, H. M. L.; Smith, H. D. (Synth. Commun., 1987)

(untitled) - Popic, V. V.; Korneev, S. M.; Nikolaev, V. A.; Korobitsyna, I. K. (Synthesis, 1991)

Patent of the USSR - Nikolaev, V. A.; Korobitsyna, I. K. (Procedure for preparation of 2-diazo-1,3-dioxoceclopentene, 1985)

(untitled) - Oda, M.; Kasai, M.; Kitahara, Y. (Chem. Lett., 1977)

(untitled) - Csizmadia, I. G.; Houlden, S. A.; Meresz, O.; Yates, P. (Tetrahedron, 1969)

Principles of molecular photochemistry: an introduction - Turro, N. J.; Ramamurthy, V.; Scaiano, J. C. (University Science Books, 2009)

(untitled) - Candeias, N. R.; Gois, P. M. P.; Veiros, L. F.; Afonso, C. A. M. (J. Org. Chem., 2008)

(untitled) - Buchner, M. R.; Wahl, B.; Ruhland, K. (J. Photochem. Photobiol., A, 2013)

(untitled) - Rau, H.; Bokel, M. (J. Photochem. Photobiol., A, 1990)

(untitled) - Corey, E. J.; Felix, A. M. (J. Am. Chem. Soc., 1965)

(untitled) - Chang, J. A.; Chiang, Y.; Keeffe, J. R.; Kresge, A. J.; Nikolaev, V. A.; Popik, V. V. (J. Org. Chem., 2006)

(untitled) - Amice, P.; Conia, J. M. (Tetrahedron Lett., 1974)

(untitled) - Kniep, C. S.; Padias, A. B.; Hall, H. K., Jr (Tetrahedron, 2000)

(untitled) - Bogdanova, A.; Popik, V. V. (J. Am. Chem. Soc., 2003)

(untitled) - Bogdanova, A.; Popik, V. V. (J. Am. Chem. Soc., 2003)

(untitled) - Nikolaev, V. A.; Frenkh, Y.; Korobitsyna, I. K. (J. Org. Chem. USSR, 1978)

Photochemistry of organic compounds: from concepts to practice - Klan, P.; Wirz, J. (Wiley, 2009)

(untitled) - Maas, G.; Krebs, F.; Werle, T.; Gettwert, V.; Striegler, R. (Eur. J. Org. Chem., 1999)

(untitled) - Hudlicky, T.; Ranu, B. C.; Naqvi, S. M.; Srnak, A. (J. Org. Chem., 1985)

(untitled) - Hudlicky, T.; Sheth, J. P.; Gee, V.; Barnvos, D. (Tetrahedron Lett., 1979)

(untitled) - Palatinus, L.; Chapuis, G. (J. Appl. Crystallogr., 2007)

(untitled) - Palatinus, L.; van der Lee, A. (J. Appl. Crystallogr., 2008)

(untitled) - Palatinus, L.; Prathapa, S. J.; van Smaalen, S. (J. Appl. Crystallogr., 2012)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. A: Found. Crystallogr., 2008)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. A: Found. Adv., 2015)

(untitled) - Dolomanov, O. V.; Bourhis, L. J.; Gildea, R. J.; Howard, J. A. K.; Puschmann, H. (J. Appl. Crystallogr., 2009)